Neuropathologic findings in a young woman 4 years following declaration of brain death: case analysis and literature review. Issue 1 (15th December 2022) - Folkerth, Rebecca D; Crary, John F; Shewmon, D Alan
Abstract: Brain death (death by neurologic criteria) is declared in 2% of all in-hospital deaths in the United States. Published neuropathology studies of individuals maintained on cardiorespiratory support are generally decades old, and notably include only 3 cases with long intervals between brain and "somatic" death (68 days, 101 days, 20 years). Here, we share our observations in a young woman supported for nearly 4½ years following declaration of brain death after oropharyngeal surgery. While limited by tissue availability and condition, we found evidence of at least partial perfusion of the superficial cerebral and cerebellar cortices by external carotid and vertebral arteries (via meningeal and posterior pharyngeal branches), characterized by focal cellular reaction and organization. Dural venous sinuses had thrombosis and recanalization, as well as iron deposition. In nonperfused brain areas, tissue "mummification, " akin to that seen in certain postmortem conditions, including macerated stillbirths and saponification (adipocere formation), was identified, and are reviewed herein. Unfortunately, correlation with years-earlier clinical and radiographic observations was not possible. Nevertheless, we feel that our careful neuropathologic inspection of this case expands the understanding of the spectrum of human brain tissue alterations possible in a very rarely seen set of conditions.